O adjetivo sob um olhar enunciativo no texto publicitário : a contribuição de Émile Benveniste - Valério, Patrícia da Silva (2005)
This research has as the main goal to study the adjective present in advertising texts collected from current Brazilian magazines in a enunciative perspective base on the Theory of Enunciation developed by Èmile Benveniste. So, this study is divided in four sections. The first one shows a review of the adjective groups using seven different Portuguese grammars, six of them normative and one of them of usage. In this part it is shown the different way each author presents the adjectives in the different studies. The second one shows the theory which guides this study: the Theory of the Enunciation as it is presented by Benveniste, the enunciation, according to the author, is something unic and unrepeatable. It is based on the instauration of an I (speaker) who assumes the speech as an I directing to a you , condition that is reversible in a determined time and space. Together (persons, time and place) they build the structure of the enunciation. The third section is all about the advertising text, its structure and characteristics , once this section is an important part of the study. The fourth and the last one is about the description of the meaning of the adjective present in the advertising texts. It is important to remember that even tough the adjective is part of a group and normally it is a reference in the speech it just has a meaning in the speech itself. Once we know that the speaker is in charge of being the main tool of the language itself announcing that it is the I and acting as a you (speaker) in the speech, we could realize, in this process, the adjective shows the subjectivity of the speaker in the enunciation